PENGEMASAN, PELABELAN DAN PEMASARAN DIGITAL PADA KELOMPOK KULINER PONDOKAN KELANA - Sandra, Evita; Deryanto, Deryanto; Afriyani, Dhea; Sukma, Dinny; Adistia, Firly; Mario, Mario; Sheng, Mao; Azroy, Muhammat; Rafiq, Muhammad; Putri, Septiana Yusnita; Wahyuni, Sri; Suseno, Tri Joko; Ramadhani, Viana Nurwidi (P3M STIE Pembangunan Tanjungpinang, 2025)
Micro, Small, and Medium Enterprises (UMKM) are part of the important role in improving the country's economy. Along with the development of the increasing times, the quantity of the MSME sector also needs to be accompanied by improving the quality produced by increasing the competitiveness of products in the market, especially when viewed in terms of packaging, labelling and digital marketing. One of the micro businesses is the Kelana Pondok Culinary Group business which is located in the village of Penaga by producing lampam cakes. The problems faced by the Pondok Kelana Culinary Group business are that the packaging is still simple, unattractive product labels and product marketing that still covers certain areas and there is no product promotion. The purpose of this activity is to carry out packaging, labelling and digital marketing in the Pondokan Kelana Culinary Group business to increase the selling value of the products it produces. The realisation of problem solving faced by the Pondok Kelana Culinary Group business is to create social media accounts, update product packaging and labels, and promote lampam cake products on social media. The problem solving method used is by conducting training, socialisation and mentoring so that the Pondokan Kelana Culinary Group business is skilled and able to process, package, and market lampam cake products digitally. The results of this activity are in the form of updated packaging and product labels to be safer and more attractive, then the lampam cake business can be promoted on social media that has been created by the author for the Kelana Pondokan Culinary Group business in order to increase lampam cake sales and attract buyer interest.